Drug Culture - Pavićević, Olivera; Ilijić, Ljeposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The subject of this paper addresses the question of what constitutes a drug culture today. Although it appears as a subculture compared to a dominant culture, it will be referred to in the paper as a drug culture, as an isolated cultural phenomenon with a specific form and contained. Drug culture research aims to understand cultural meanings and develop cultural competence as an exploratory approach and procedure that looks at the qualitative dimension of psychoactive substance use. Cultural competence forms part of a research-therapeutic approach in the treatment of psychoactive substance abuse. It is realized through an appreciation of diversity as a characteristic among cultural situations (socio-economic, ethnic, racial, gender, geographical, sexual and ultimately consumer). Cultural competence represents and develops the ability to know, understand and respect the beliefs of individuals who participate in treatment (both donors and recipients). Cultural competence is a dynamic, ongoing and developmental process that requires long-term commitment and is achieved over time (SAMSHA, 2014). Understanding consumer cultural practices is based on knowledge of the socio-cultural traits and meanings of those practices and the ability to access prevention, therapy and rehabilitation based on these.